The Effect Of Accounting Information At Explaining Stock Prices - المصطفى, علي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The current study aims to examine the impact of the Syrian pound exchange rate changes against USD, on the relevance of accounting information for companies listed at Damascus stock market Finance. During the period from the first quarter of 2010 to the third quarter of 2019. The study applied on banks listed on Damascus Stock Exchange before 2010. To reach search objects, the price and return models have been applied to the Final data for The banking sector to test the research hypothesis and discuss the results. The research found a moral effect on the changes in the exchange rate SYP against dollar ,The appropriateness of accounting information in interpreting stock prices listed companies on the Damascus Stock Exchange. The research concludes with a set of recommendations, the most important of which is to use the price model with a justed to The exchange rates of the SYP against the dollar for companies listed in Damascus market For securities.